Investigation of stearic acid additive effects on the mechanochemical synthesis of silver nanoparticles. Issue 2 (28th February 2017) - Khakan, Behruz; Shahroozi, Abbas; Afsari, Ahmad; Hosseini, Seyed Reza
Abstract : The silver (Ag) powder was synthesized in a mechanochemical (MC) process by inducing a solid-state displacement reaction between silver chloride (AgCl) and copper (Cu). This process was carried out in argon atmosphere conditions using a planetary ball mill. The reaction caused the mixture of AgCl and Cu to change the composition of the mixture to Ag and copper chloride (CuCl). CuCl was separated from MC product by leaching with ammonium hydroxide. Thus, Ag powder was obtained as the final product. Stearic acid (C18 H36 O2 ) was used as the additive to improve dispersion of Ag powder during the MC process. The ground powders, formed in the presence and absence of additive, were characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM). The XRD determined that the reaction between AgCl and Cu was completed in 18 h milling. SEM and particle size analysis examinations revealed that the size of the particles in the synthesized metallic Ag powder was in the range of 30–300 nm.